PERSEPSI MAHASISWA SEMESTER AWAL TERHADAP KEGIATAN PRAKTIKUM BIOLOGI PADA KURIKULUM OBE - Astuti Muh. Amin; Romi Adiansyah; Noor Hujjatusnaini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The implementation of Outcome-Based Education (OBE) positions laboratory practice as an essential component in creating meaningful learning experiences that support the achievement of learning outcomes. Although OBE has been widely adopted in higher education, evidence regarding how first-year students perceive laboratory implementation remains limited. This study explored students' perceptions of the General Biology Laboratory course in supporting the implementation of OBE at the Biology Education Study Program of IAIN Ternate. A mixed-methods approach with a convergent design was employed by involving all students who had completed the laboratory course through a total sampling technique. Data were collected using a Likert-scale questionnaire, structured interviews, observations, and document analysis, and were analyzed descriptively using percentages, complemented by qualitative data analysis. The findings revealed consistently positive perceptions across all evaluated dimensions, including laboratory planning, implementation, facilities and infrastructure, perceived benefits, scientific skill development, and support for OBE implementation. These findings suggest that laboratory learning has contributed to strengthening students' academic competencies and scientific skills in alignment with the intended learning outcomes. Furthermore, the study provides empirical evidence to support the continuous improvement of General Biology laboratory practices, particularly in refining laboratory modules, optimizing time management, and strengthening assessment systems to enhance the effectiveness and sustainability of OBE implementation. ABSTRAK Implementasi Outcome-Based Education (OBE) menempatkan kegiatan praktikum sebagai bagian penting dalam membangun pengalaman belajar yang mendukung ketercapaian learning outcomes. Meskipun penerapan OBE semakin luas di perguruan tinggi, informasi mengenai bagaimana mahasiswa memaknai pelaksanaan praktikum, khususnya pada semester awal, masih relatif terbatas. Penelitian ini mengeksplorasi persepsi mahasiswa terhadap pelaksanaan Praktikum Biologi Umum dalam mendukung implementasi OBE di Program Studi Tadris Biologi IAIN Ternate. Pendekatan mixed methods dengan desain konvergen digunakan melalui pelibatan seluruh mahasiswa yang telah mengikuti praktikum menggunakan teknik total sampling. Data diperoleh melalui angket skala Likert, wawancara terstruktur, observasi, dan dokumentasi, kemudian dianalisis secara deskriptif menggunakan persentase serta diperdalam melalui analisis data kualitatif. Persepsi mahasiswa menunjukkan kecenderungan positif pada aspek perencanaan, pelaksanaan, sarana dan prasarana, manfaat praktikum, pengembangan keterampilan ilmiah, serta dukungan terhadap implementasi OBE. Temuan tersebut memperlihatkan bahwa pengalaman belajar di laboratorium telah berkontribusi terhadap penguatan kompetensi akademik dan keterampilan ilmiah yang selaras dengan learning outcomes. Penelitian ini menawarkan dasar empiris bagi evaluasi dan penyempurnaan penyelenggaraan praktikum, terutama pada pengembangan modul, pengelolaan waktu, dan sistem penilaian agar implementasi OBE berlangsung secara lebih efektif dan berkelanjutan.